The impact of Additional Tax Collection implementation for regional government and taxpayer - Muhammad Syafei; Hamdani Hamdani; Haryadi Haryadi; Oktavani Yenny (Cita Konsultindo Research Center, 2024)
The government has issued Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments (HKPD), the aim of which is to strengthen local taxing power and improve the quality of regional spending to make it more efficient, productive, and accountable. One of the policies related to regional taxation regulated in the HKPD Law is the existence of an additional tax collection policy. However, this policy has an impact on district governments, provincial governments, and taxpayers because of the increase in PKB payments and PKB additional tax collection. The aim of this research is to discuss the impact of regional tax option policies on regional governments and taxpayers. The method used is normative legal research. Data sources consist of primary legal materials, secondary legal materials, and tertiary legal materials. In this research, the data is analyzed qualitatively and then presented descriptively to obtain comprehensive conclusions. The research results show that the existence of additional tax collection PKB and BBNKB has a positive impact on Regency/City Governments, while provincial governments can have an impact on income decreasing, remaining constant, and even increasing. Meanwhile, for taxpayers, there is a tendency for the burden to increase or there is an increase in PKB and BBNKB payments, but it could also be the same compared to the previous year. This depends on the amount of the PKB tariff set by the provincial government in the PDRD Regional Regulation.